Estimate Hyoscine Butylbromide and Mefenamic Acid by RP-HPLC Method Development and Accelerated Stability Study in Pure and Combine Dosage Form. Issue 4 (2018) - Tandel, Jinal N.; Patel, Jatin; Patel, Rashmika R.; Shah, Samir K.
No abstract available